Safety in the Classroom: Safeguarding Liberal Arts Education from the Neo-Liberal Threat - Dylan, Arielle (Canadian Journal of Higher Education, 2012)
This article examines the elusive concept of safety in liberal arts classrooms which are often contoured by a plurality of social, cultural, political, psychological, historical, and discursive forces and performances. Using select principles from adult education and social work with groups as an organizing metaphor, the article discusses the classroom as a large group, the changing student body, and, especially, the impact of diversity and inclusivity in liberal arts settings. Because the aim of liberal arts education is usually to promote independent and critical thinking, open-mindedness, and greater communication and decision-making skills, its goals foster, to a great degree, citizen engagement that empowers persons to participate in collective actions toward greater equality and justice in communities both locally and globally. Classroom safety is essential to these aims because it increases opportunity for free, critical, and independent thought necessary for progressive, egalitarian, and justice pursuits. The article explores safety, including dialogic practices and reflection on relations of power within the classroom, for its significant role in fulfilling liberal arts aspirations.